What magnitude of force is a slopestyle skier exposed to when landing a Big Air jump? - Löfquist, S.; Björklund, G. (International Journal of Exercise Science, 2020)
The purpose of this study was to investigate the magnitude of force a slopestyle skier is exposed to when landing either forward or switch in a big air jump. Ten male freeskiers (age 23 ± 6 years; height 179.2 ± 5.4 cm; body mass 72.5 ± 8.6 kg; mass of equipment 16.7 ± 1.4 kg; total mass 89.2 ± 8.6 kg) participated and each performed five 180 jumps and five switch 180 jumps in a randomized order. Forces were quantified using pressure insoles. The results showed a force of 1446 ± 367 N (2.04 ± 0.46 times body mass) for the 180 jump and a force of 1409 ± 257 N (1.99 ± 0.28 times body mass) for the switch 180 jump. There was no difference in force between the 180 jump and the switch 180 jump, p=0.582. There was a trend for the switch 180 for a correlation between a heavier body mass and a greater force (r = 0.604, r2= 0.365, p = 0.064) as well as a heavier total mass and a greater force (r = 0.621, r2= 0.385, p = 0.055). This study shows that the force when landing a big air jump is roughly twice the slopestyle skier`s body mass, but no difference in force was seen between performing a 180 or a switch 180 jump. The force of twice the body mass could therefore be considered a minimum value for slopestyle skiing.